Penyusunan Profil Dusun sebagai Upaya Updating Data untuk Pembangunan Desa - Yusliana, Yusliana (Retii, 2024)
The Minister of Home Affairs Regulation No. 12 of 2007 concerning Guidelines for the Preparation and Utilization of Village and Sub-district Profile Data regulates the mechanism and instruments for compiling village profiles, which is a crucial step in mapping village potentials and problems. We can use village profile data to identify village opportunities and problems. We will then use this information as a basis for creating development programs. This community service activity aims to assist Kowen II Hamlet, Timbulharjo Village, Sewon District, Bantul Regency, in compiling a profile book as part of an effort to map the development of hamlet data and information. This process has resulted in the Kowen II Hamlet Profile Book, which can complement the village profile and provide the latest data for the government and the community.